Prospective Randomized Controlled Clinical Trial Comparing Hyperosmolar Saline to Standard Isotonic Irrigation Fluid for Arthroscopic Knee Surgery. Issue 7 (31st July 2020) - Stannard, James; Smith, Matthew; Ma, Richard; Skelley, Nathan; Sherman, Seth; Ray, Taylor; Cook, James; Oladeji, Lasun
Objectives: Knee arthroscopy using isotonic irrigation fluids is performed safely in millions of patients each year. However, arthroscopic procedures can disrupt the native biology of the joint when hyperosmolar synovial fluid (400 mOsm/L) is replaced by isotonic irrigation fluid (270-300 mOsm/L). Potential ramifications include cell apoptosis and necrosis, alterations in gene expression, protein synthesis and calcium signaling, and extracellular matrix compositional changes with resultant material property perturbations. Recent in vitro studies suggest higher osmolarity irrigation fluids potentiate a chondroprotective environment and a clinical study using hyperosmolar saline for shoulder arthroscopy reported potential clinical advantages. To date, there are no studies examining the use of a hyperosmolar irrigation solution in patients undergoing knee arthroscopy to the authors' knowledge. Therefore, this prospective randomized double-blind controlled clinical trial was designed to assess safety and efficacy of a hyperosmolar irrigation solution in patients undergoing arthroscopic knee surgery. Methods: With institutional review board approval and informed consent, adult patients scheduled to undergo arthroscopic knee surgery (i.e., chondroplasty, diagnostic, meniscectomy, meniscus repair) were randomized to surgery with either isotonic Lactated Ringer's (273mOsm/L) or hyperosmolar saline (593 mOsm/L) irrigation solution. The hyperosmolar solution was created by adding 120cc of 23.4% NS solution to a 3L bag of 0.9% NS (Figure). Primary outcomes included perioperative blood pressure, knee girth, pain, and narcotic pain medication consumption. Blood pressure and knee girth measurements were performed before and after surgery. Visual Analogue Scale (VAS) pain scores and narcotic pain medication consumption were logged on post-operative days (POD) 1-3. Data from each cohort were pooled and analyzed for statistical significance (P<0.05) using an unpaired t-Test. Results: (Table): Forty-four patients underwent arthroscopic knee surgery with isotonic (N=23) or hyperosmolar (N=21) irrigation fluid. There were 11 males and 12 females (mean age 44.0 years) in the isotonic cohort and 7 males and 14 females (mean age 40.4 years) in the hyperosmolar cohort. There were no significant differences with respect to surgical duration (pump time), however, significantly (p=0.04) more irrigation fluid was used to complete the procedures in the isotonic cohort compared to the hyperosmolar cohort. There were no significant differences with respect to change in knee girth or blood pressure. There were no significant differences in VAS pain scores or narcotic medication consumption. Conclusion: The results of this randomized clinical trial suggest that the hyperosmolar irrigation solution used is safe for patients undergoing arthroscopic knee surgery. Less irrigation fluid was required when using the hyperosmolar solution with no apparent detrimental effects on execution of the surgical procedure, postoperative pain, or narcotic use. Taken together with previous studies showing chondroprotective and potential clinical benefits in arthroscopic shoulder surgery, the use of hyperosmolar saline irrigation fluid can be considered for clinical use in patients undergoing knee arthroscopy. Figure 1. Table 1. Demographic and Outcome Results Parameter Isotonic (n=23) Hyperosmolar (n=21) P Age (years) 44.0+13.8 40.4+11.5 0.34 Sex 11M/12F 7M/14F 0.37 Pre-Op Blood Pressure 139/88 123/78 Post-Op Blood Pressure 136/83 123/76 Change in Knee Girth (cm) 1.20+1.1 1.6+1.2 0.23 Surgical Time (min) 51.2+34.3 40.3+15.0 0.18 Irrigation Fluid Used (mL) 7374+4822 4823+2719 0.04 Amount of IVF (mL) 889+491 846+370 0.75 VAS Pain (POD 1) 4.8+2.0 4.9+2.0 0.90 VAS Pain (POD 2) 4.8+2.5 3.9+1.7 0.17 VAS Pain (POD 3) 3.8+1.7 3.8+1.9 0.90 Narcotic Pills Consumed (POD 1) 2.9_2.1 2.7+2.3 0.84 Narcotic Pills Consumed (POD 2) 2.5+2.5 2.6+3.2 0.84 Narcotic Pills Consumed (POD 3) 2.3+2.6 1.1+2.0 0.15